ANALISIS KESESUAIAN STANDAR PELAYANAN TEMPAT PENITIPAN ANAK (TPA) YAYASAN BUAH HATI SIDOARJO DENGAN STANDAR NASIONAL - Yussi Ramawati (Universitas Musamus,Merauke,Papua, 2016)
This study is aimed to investigate service standard at daycare Yayasan Buah Hati (TPA YBH) and analyze the appropriateness of it to national service standard. This study applied case study to investigate the unit of analysis, that is service standard at TPA YBH by using four dimension of national service standard of daycare, they are: standard of child growth achievement, standard of infrastructure, management, and financing, standard of education personnels, standard of content, process, and evaluation. The data was collected by conducting in-depth interview, observation, and documentation. Then, all data was analyzed by implementing descriptive qualitative analysis. The result of this study shows that service standard at TPA YBH has included all dimension of national service standard of daycare in Indonesia. Yet, practically, TPA YBH implemented service standards of daycare in which have not fulfilling the national standard. For instance, in determining the maximum age of children, TPA YBH determined 9 years as maximum age that can be registered at TPA YBH; while national standard said that maximum age is 6 years old. In financing sector, TPA YBH has not used government subsidy, while in nation standard, a daycare can use government subsidy as the financial sources. Overall, TPA YBH has been fulfilled the national standard for the dimension standard of infrastructure and management, standard of education personals, standard of content, process, and evaluation.